Heparan Sulfate Proteoglycans as Emerging Players in Synaptic Specificity - Condomitti, Giuseppe; de Wit, Joris (Frontiers in Molecular Neuroscience, 2018)
Neural circuits consist of distinct neuronal cell types connected in specific patterns. The specificity of these connections is achieved in a series of sequential developmental steps that involve the targeting of neurites, the identification of synaptic partners, and the formation of synapses. Cell-surface proteins play a critical role in each of these steps. The heparan sulfate proteoglycan (HSPG) family of cell-surface proteins is emerging as a key regulator of connectivity. HSPGs are expressed throughout brain development and play important roles in axon guidance and synapse development. New insights indicate that distinct neuronal cell types express unique combinations of HSPGs and heparan sulfate-modifying enzymes. Furthermore, HSPGs interact with cell type-specific binding partners to mediate synapse development. These observations suggest that cell type-specific repertoires of HSPGs, specific patterns of heparan sulfate modifications on the cell surface, and select interactions with binding partners contribute to the development of specific synaptic connectivity. Genome-wide association studies have linked these proteins to neurodevelopmental and neuropsychiatric diseases, indicating that HSPGs play an essential role in neural circuit development, and that their dysfunction may be involved in the development of brain disorders.